Ultrasound endonasal dacryocystorhinostomy in the treatment of recurrent dacryocystitis in newborns - K.G. Naumov; M.I. Shlyakhtov; M.G. Kataev (Офтальмохирургия)
Purpose. To evaluate early and long-term functional and anatomic results of surgical treatment of lacrimal pathways obstruction (LPO) in children with endonasal dacryocystorhinostomy (EDCR) method using ultrasound bone tissue dissector for the formation of nasolacrimal anastomosis. Material and methods. Surgical treatment of recurrent dacryocystitis of newborn (DN) after repeated unsuccessful «blind»lacrimal pathways probing in children with nasolacrimal duct obstruction, including cases of congenital nasolacrimal duct atresia. Bone «window» of the nasolacrimal anastomosis during endoscopic EDCR was formed using SONOCA 185 piezoelectric ultrasound dissector. In total, 14 children, 8 girls and 6 boys aged from 3 to 11 years (mean, 6 years) were operated with follow-up period of 6 months. Results. It was found that in all the children an adequate nasolacrimal anastomosis was formed without significant bleeding episodes both intraoperatively and in the early post-op period. No cases of destruction of the medial wall of the lacrimal sac were marked. Functional success was achieved in 92.8% (13 of14 cases). In 7.2% (1 of 14cases) there was a postoperative granuloma of the mucous in the rhinostoma region which was a partial obstacle for tear flow. Conclusions. Controlled low temperature process of nasal bones ultrasound dissection during EDCR in children allows formation of an adequate bone «window»and, therefore, a valuable nasolacrimal anastomosis in narrow nasal passages, makes the surgical procedure much easier and quicker, enables better healing of soft tissues in a shorter period.